UKRAINIANS IN KAZAKHSTAN DURING COLLECTIVIZATION, DEKULAKIZATION, AND THE HOLODOMOR OF 1932–1933 (Південний архів (історичні науки), 2024)
This article explores the repressions directed against Ukrainians–settlers and special settlers in the Kazakh ASSR– during the Great Famine, known as Asharshylyk. It focuses on the transformations in the lives of Ukrainian settlers in Kazakhstan beginning with the onset of collectivization and dekulakization in 1930, leading to economic decline and famine between 1931 and 1934. During the Holodomor of 1932–1933, Ukrainians from the Ukrainian SSR and Kuban were also forcibly relocated to Kazakhstan as special settlers, where they were forced to endure harsh conditions in an unforgiving climate, laboring in mines and quarries, and became victims of famine. They shared in the suffering of the Kazakh people during the Asharshylyk–the Kazakh famine of 1931–1934. Objective: To analyze the experiences of Ukrainian settlers and special settlers in Kazakhstan during the Holodomor and Asharshylyk. Methodology: An analysis of materials on repressed Ukrainians in the Kazakh ASSR during the famine period offers insight into the number of Ukrainians deported, their survival practices, and the challenges in interethnic relations. Research Results: The study examines the changes in the lives of Ukrainian settlers in Kazakhstan with the onset of collectivization, dekulakization, and famine; the geographic patterns of deportation of dekulakized Ukrainians in Kazakhstan; the causes and consequences of famine among Ukrainian farmer-settlers; and the nature of interethnic conflicts and their impact on the policy of Ukrainization in Kazakhstan. Conclusions: Unlike the 1932–1933 Holodomor in Ukraine, the famine in Kazakhstan is considered a consequence of the forced sedentarization of Kazakhs imposed by the Stalinist regime. At the same time, Kazakhstan was home to a significant population of Ukrainian farmers and special settlers who also fell victim to famine. Their presence was initially part of an imperial policy aimed at colonizing Kazakh lands, which resulted in the reduction of the Kazakh living space. Between the late 19th century and 1926, the Ukrainian population in Kazakhstan grew from 80–120 thousand to 860 thousand. However, Ukrainian settlers proved highly vulnerable: the policy of “liquidating the kulaks as a class” and forced collectivization with the collectivization of all assets destroyed community life and the traditions that had sustained them in the harsh climate. Their numbers were gradually supplemented by special settlers–compatriots and Ukrainians from Kuban and other Ukrainian communities in the RSFSR. Special settlers were forced to work in mines and quarries, falling victim to famine due to poor nutrition and living conditions. Due to repression, famine, and deportations, the Ukrainian population in Kazakhstan decreased by 23.5% from 1926 to 1939. Amid the dehumanization resulting from hunger and repression, ethnic conflicts occurred, with Kazakhs often falling victim. Since Soviet authorities perceived the Ukrainian national movement as a threat, this led to the rollback of the korenizatsiya (Ukrainization) policy in the Kazakh ASSR in favor of «implanting Leninist internationalism».
Keywords: repression, 1932–1933 famine, collectivization, dekulakization, Ukraine, Kazakhstan, Holodomor, Asharshylyk